Allelic Dropout Is a Common Phenomenon That Reduces the Diagnostic Yield of PCR-Based Sequencing of Targeted Gene Panels - Shestak, Anna G.; Bukaeva, Anna A.; Saber, Siamak; Zaklyazminskaya, Elena V. (Frontiers in Genetics, 2021)
Primary cardiomyopathies (CMPs) are monogenic but multi-allelic disorders with dozens of genes involved in pathogenesis. The implementation of next-generation sequencing (NGS) approaches has resulted in more time- and cost-efficient DNA diagnostics of cardiomyopathies. However, the diagnostic yield of genetic testing for each subtype of CMP fails to exceed 60%. The aim of this study was to demonstrate that allelic dropout (ADO) is a common phenomenon that reduces the diagnostic yield in primary cardiomyopathy genetic testing based on targeted gene panels assayed on the Ion Torrent platform. We performed mutational screening with three custom targeted gene panels based on sets of oligoprimers designed automatically using AmpliSeq Designer® containing 1049 primer pairs for 37 genes with a total length of 153 kb. DNA samples from 232 patients were screened with at least one of these targeted gene panels. We detected six ADO events in both IonTorrent PGM (three cases) and capillary Sanger sequencing (three cases) data, identifying ADO-causing variants in all cases. All ADO events occurred due to common or rare single nucleotide variants (SNVs) in the oligoprimer binding sites and were detected because of the presence of ‘marker’ SNVs in the target DNA fragment. We ultimately identified that PCR-based NGS involves a risk of ADO that necessitates the use of Sanger sequencing to validate NGS results. We assume that oligoprimer design without ADO data affects the amplification efficiency of up to 0.77% of amplicons.